Neutrophil Gelatinase–Associated Lipocalin Protects from ANCA-Induced GN by Inhibiting T(H)17 Immunity - Schreiber, Adrian (J Am Soc Nephrol, 2020)
BACKGROUND: Neutrophil gelatinase–associated lipocalin (NGAL) is a diagnostic marker of intrinsic kidney injury produced by damaged renal cells and by neutrophils. ANCA-associated vasculitis features necrotizing crescentic GN (NCGN), and ANCA-activated neutrophils contribute to NCGN. Whether NGAL plays a mechanistic role in ANCA-associated vasculitis is unknown. METHODS: We measured NGAL in patients with ANCA-associated vasculitis and mice with anti-myeloperoxidase (anti-MPO) antibody–induced NCGN. We compared kidney histology, neutrophil functions, T cell proliferation and polarization, renal infiltrating cells, and cytokines in wild-type and NGAL-deficient chimeric mice with anti-MPO antibody–induced NCGN. To assess the role of T(H)17 immunity, we transplanted irradiated MPO-immunized MPO-deficient mice with bone marrow from either wild-type or NGAL-deficient mice; we also transplanted irradiated MPO-immunized MPO/IL-17A double-deficient mice with bone marrow from either IL-17A–deficient or NGAL/IL-17A double-deficient mice. RESULTS: Mice and patients with active ANCA-associated vasculitis demonstrated strongly increased serum and urinary NGAL levels. ANCA-stimulated neutrophils released NGAL. Mice with NGAL-deficient bone marrow developed worsened MPO-ANCA–induced NCGN. Intrinsic neutrophil functions were similar in NGAL-deficient and wild-type neutrophils, whereas T cell immunity was increased in chimeric mice with NGAL-deficient neutrophils with more renal infiltrating T(H)17 cells. NGAL-expressing neutrophils and CD3(+) T cells were in close proximity in kidney and spleen. CD4(+) T cells showed no intrinsic difference in proliferation and polarization in vitro, whereas iron siderophore–loaded NGAL suppressed T(H)17 polarization. We found significantly attenuated NCGN in IL-17A–deficient chimeras compared with MPO-deficient mice receiving wild-type bone marrow, as well as in NGAL/IL-17A–deficient chimeras compared with NGAL-deficient chimeras. CONCLUSIONS: Our findings support that bone marrow–derived, presumably neutrophil, NGAL protects from ANCA-induced NCGN by downregulating T(H)17 immunity.